2011
DOI: 10.1002/chin.201134262
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Chemical Constituents of Plants from the Genus Rhododendron

Abstract: Review: 87 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…baeticum (Boissier & Reuter) Handel-Mazzetti), and some introgression has occurred between R. ponticum and congenerics in parts of Britain (Milne & Abbott 2000), but most likely not in Ireland Stout et al 2015). As in other Ericaceous genera, rhododendrons produce toxic diterpene secondary metabolites known as grayanotoxins [GTXsreviewed in Qiang, Zhou & Gao (2011)], which are characterized by a polyhydroxylated tetracyclic ring structure. GTXs have a neurotoxic mode of action blocking sodium channel receptors and preventing their inactivation (Takeda & Narahashi 1988).…”
Section: Introductionmentioning
confidence: 99%
“…baeticum (Boissier & Reuter) Handel-Mazzetti), and some introgression has occurred between R. ponticum and congenerics in parts of Britain (Milne & Abbott 2000), but most likely not in Ireland Stout et al 2015). As in other Ericaceous genera, rhododendrons produce toxic diterpene secondary metabolites known as grayanotoxins [GTXsreviewed in Qiang, Zhou & Gao (2011)], which are characterized by a polyhydroxylated tetracyclic ring structure. GTXs have a neurotoxic mode of action blocking sodium channel receptors and preventing their inactivation (Takeda & Narahashi 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Plants 2020, 9, 338 2 of 16 potential genetic resources for the development of new cultivars that can adapt to diverse environmental conditions [4]. In addition, plants in the genus Rhododendron L. produce numerous chemical constituents and are recognized as an important source of bioactive phytochemicals [5]. Some Rhododendron species are used as traditional medicine in China, India, Europe, and North America against various diseases, such as inflammation, pain, skin ailments, common cold, and gastrointestinal disorders [5].…”
mentioning
confidence: 99%
“…In addition, plants in the genus Rhododendron L. produce numerous chemical constituents and are recognized as an important source of bioactive phytochemicals [5]. Some Rhododendron species are used as traditional medicine in China, India, Europe, and North America against various diseases, such as inflammation, pain, skin ailments, common cold, and gastrointestinal disorders [5]. However, as an important natural resource for human daily life and ecosystem composition, most Rhododendron species are facing risk of extinction due to the high frequency of anthropogenic disturbance [6].…”
mentioning
confidence: 99%
“…Naoyanghua is also used as an insecticidal plant and is widely distributed in Jiangsu, Fujian, Guangdong and Sichuan provinces in China (Cheng and Hu, 1998;Zhong and Hu, 2000). The results of phytochemical investigations of this plant showed that flavonoids and diterpenoids were the main bioactive constituents, with triterpenoids, lignans, phenolic glycosides, coumarins, quinones and steroids also present (Qiang et al, 2011). According to the literature, flavonoids are the major compounds found in flowers of R. molle, making up about 8.87% of the dry plants (Zhu and Hu, 2011), while diterpenoids were found in trace amounts only.…”
Section: Introductionmentioning
confidence: 93%